Analisis Dampak Produktivitas Sektoral Terhadap Kesejahteraan Masyarakat Di Bolaang Mongondow Raya Periode 2017-2023 - Putri Silvia Suleman; Syarwani Canon; Boby Rantow Payu (Jurnal Economic Resource, 2026)
This study aims to analyze the impact of sectoral productivity on community welfare in Bolaang Mongondow Raya during the period 2017–2023. Community welfare in this study is proxied by per capita expenditure. The independent variables used include primary, secondary, and tertiary sector productivity, while the human development index is used as a moderating variable. This study is quantitative in nature, using secondary data obtained from the Central Statistics Agency (BPS). The analysis was conducted using panel data regression with the Fixed Effect Model (FEM) approach. The results show that sectoral productivity has a varying effect on community welfare. Primary sector productivity has a positive and significant effect on community welfare, while secondary and tertiary sector productivity has a positive but insignificant effect. In addition, the Human Development Index (HDI) has not been proven to significantly moderate the relationship between sectoral productivity and community welfare, even though the direction of the effect is positive. This indicates that improvements in human resource quality have not been fully accompanied by improvements in economic competitiveness in the region. This study confirms that the economy of Bolaang Mongondow Raya is still dependent on the primary sector. Efforts to improve community welfare need to be accompanied by strengthening productivity in the secondary and tertiary sectors and improving the quality of human development so that the resulting economic growth is inclusive and sustainable